Effectiveness of oil pulling therapy in reduction of radiation Induced xerostomia among patients with head and neck Cancer receiving radiation therapy - P. DAVID ROBINSON (International Journal of Pharma and Bio Sciences, 2017)
Hyposalivation is a common sequel in patients undergoing irradiation for malignant tumors of the head & neck. The lack of salivary secretions impacts the ability to eat, sleep, speak, and swallow. It is the responsibility of oncology nurse to play a critical role in the prevention, identification, and management of side effects, including xerostomia. The main objectives are to assess the pretest level of radiation induced xerostomia among patients with head and neck cancer in experimental and control group and to determine the effectiveness of oil pulling therapy in reduction of radiation induced xerostomia among patients with head and neck cancer in experimental group. Quasi experimental with experimental and control group, pretest-posttest design was chosen for the study. A total of 40 head and neck cancer patients receiving radiation therapy were selected by using purposive sampling technique from Erode Cancer Centre, Erode. The patients were divided into groups, 20in experimental group and 20 in control group. Descriptive and inferential statistics were used to analyze the data collected. The study results showed that there was a significant improvement in the mean score of radiation induced xerostomia (i.e. -3.05) among head and neck cancer patients on radiation therapy, who were receiving oil pulling therapy than those who were not. There is a significant decrease (P=0.0001 which is <0.001) in the level of xerostomia among head and neck cancer patients on radiation therapy, who are receiving oil pulling therapy than those who are not. The study indicates that oil pulling therapy is a simple applicable method for the prevention of radiation induced xerostomia.